Empowering Housewives in Improving Family Health Through Manufacturing Training Traditional Herbal Drink - Andy Hayun Abidin; Mujito Mujito; Ning Arti Wulandari (STIKes Patria Husada Blitar, 2026)
The transformation of the health system is focused on comprehensively addressing health problems and strengthening disease prevention. Traditional drinks in Indonesia are known as